Cost and capacity requirements of electrification or renewable gas transition options that decarbonize building heating in Metro Vancouver, British Columbia. (July 2022) - Palmer-Wilson, Kevin; Bryant, Tyler; Wild, Peter; Rowe, Andrew
Abstract: Northern countries face a unique challenge in decarbonizing heating demands. This study compares two pathways to reduce carbon emissions from building heating by (1) replacing natural gas heaters with electric heat pumps or (2) replacing natural gas with renewable gas. Optimal annual system cost and capacity requirements for Metro Vancouver, Canada are assessed for each pathway, under nine scenarios. Results show that either pathway can be lower cost but the range of costs is more narrow for the renewable gas pathway. System cost is sensitive to heat demand, with colder temperatures favouring the renewable gas pathway and milder temperatures favouring the electrification pathway. These results highlight the need for a better understanding of heating profiles and associated energy system requirements. Highlights: Compares electrification and renewable gas decarbonization pathways for heating. Hindcasts heat demand profile from electricity consumption and temperature records. Optimizes energy production and storage across demand, supply, and cost scenarios. Electrified heating requires 4 to 357 GWh of electric storage. Renewable gas pathway has lower range of costs across scenarios.